Community engagement at a higher education institution - exploring a theoretical grounding for scholarly-based service-related process - Smith-Tolken, Antoinette Rachèlle (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Curriculum Studies))--University of Stellenbosch, 2010.